2017
DOI: 10.1093/humrep/dex280
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of endocrine and genetic abnormalities in boys evaluated systematically for a disorder of sex development

Abstract: STUDY QUESTIONWhat is the likelihood of identifying genetic or endocrine abnormalities in a group of boys with 46, XY who present to a specialist clinic with a suspected disorder of sex development (DSD)?SUMMARY ANSWERAn endocrine abnormality of the gonadal axis may be present in a quarter of cases and copy number variants (CNVs) or single gene variants may be present in about half of the cases.WHAT IS KNOWN ALREADYEvaluation of 46, XY DSD requires a combination of endocrine and genetic tests but the prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 27 publications
1
31
1
Order By: Relevance
“…Whilst the prevalence of extra-genital anomalies in hypospadias has been previously reported to range from 12-46% [Schneuer et al, 2015;Fernandez et al, 2016;Lu et al, 2017], the prevalence rate of 22% reported in this study is similar to that in other large cohort studies where information on associated congenital anomalies was systematically collected [Ahmed et al, 2004;Cox et al, 2014;Nixon et al, 2017]. The pattern of extra-genital anomalies that were encountered in this cohort was also similar to that reported before with a disorder of intrauterine growth manifested as being small for gestational age [Ahmed et al, 2004;Nordenvall et al, 2014;Poyrazoglu et al, 2017].…”
Section: Discussionsupporting
confidence: 88%
“…Whilst the prevalence of extra-genital anomalies in hypospadias has been previously reported to range from 12-46% [Schneuer et al, 2015;Fernandez et al, 2016;Lu et al, 2017], the prevalence rate of 22% reported in this study is similar to that in other large cohort studies where information on associated congenital anomalies was systematically collected [Ahmed et al, 2004;Cox et al, 2014;Nixon et al, 2017]. The pattern of extra-genital anomalies that were encountered in this cohort was also similar to that reported before with a disorder of intrauterine growth manifested as being small for gestational age [Ahmed et al, 2004;Nordenvall et al, 2014;Poyrazoglu et al, 2017].…”
Section: Discussionsupporting
confidence: 88%
“…For example, DSDs may arise from either single-gene defects (>50 genes implicated) or from larger chromosomal abnormalities and combining genetic testing approaches can establish a genetic diagnosis in 40%-60% of cases. 47,57 Whole-Exome Sequencing (WES)/ Whole-Genome Sequencing (WGS). In contrast to disease-targeted gene panels, where prior knowledge of the likely causative gene is required, WES or WGS is suited to the investigation of individuals or kindreds suspected of genetic disease of unknown aetiology (ie "gene discovery" approach).…”
Section: High-content Genetic Testing and Ngs Methodsmentioning
confidence: 99%
“…In some clinical settings, gene‐panel testing is used in combination with other platforms including aCGH. For example, DSDs may arise from either single‐gene defects (>50 genes implicated) or from larger chromosomal abnormalities and combining genetic testing approaches can establish a genetic diagnosis in 40%‐60% of cases …”
Section: Germline Genetic Testing – Selecting the Optimal Testmentioning
confidence: 99%
“…Although XY DSD can be broadly categorised into disorders of gonadal development, androgen synthesis and androgen action ( Table 1), around 70% of boys who present to a specialist clinic with suspected DSD do not fit into any of these categories and are classed as a non-specific disorder of undermasculinisation [2]. It is possible that environmental factors may also play a role [3,4] and interfere with the normal development of the penis.…”
Section: Conditions Associated With Dsd In Boysmentioning
confidence: 99%
“…Interestingly, a genetic abnormality was detected in 20% of the boys with normal endocrine biochemistry [2]. Increasingly, it is therefore likely that biochemical investigations will in future be paired with molecular genetic analysis to provide a more comprehensive opportunity to offer boys a definitive diagnosis.…”
Section: Biochemical Evaluationmentioning
confidence: 99%